Integration and concertation process in Latin America. Is there just one supplementary way? - Siles del Valle, Juan Ignacio (Razón y fe, 2018)
The vocation of countries from Latin America to integration has constantly existed along its bicentennial history. After many attempts, as can be seen from the investigation, in 2010 the Community of Latin American and Caribbean States was built in Quintana Roo. This institution is meant to be the main area of joint political decision of the countries of the region as well as is meant to be the largest partner of the region in comparison with countries such as United States or with other integration systems such as European Union. All this without questioning, for now, the existence of the current and different inter-American alliances, for the way in Latin American integration is not unidirectional.